Gravura-objeto: o campo ampliado da impressão - Dias, Cristiane Peres (2020)
In this Course Conclusion Work at the Bachelor of Visual Arts, at the Federal University of Paraíba, I sought to investigate the three-dimensional impression of everyday objects, relating the sculptural results to the practice of expanded engraving. I used plastic as a production support, associating manufacturing practices, in addition to proposing a new meaning as a printing matrix. This work is based on the analysis of series of my artistic works exhibited in the “Vocabricular do Vazio” exhibition of my authorship, held in 2019 at Galeria Casarão 34, in the city of João Pessoa, Paraíba. The objective was to investigate experimental engraving by molding three-dimensional objects. I used as a theoretical basis the “Sculpture in the extended field” by Krauss (1984), Veneroso (2012), “the Fold and the Void” by Romagnolo (2018), the artistic work of Maria Bonomi engraver “From engraving to public art” organized by Laudanna (2007) and Elisa Bracher through Mammí (2012). For data collection and analysis of results I used a qualitative (GUERRA, 2006) and a/r/tographic (DIAS and IRWIN, 2013) approach, articulating bibliographic research, in reference books on printmaking, postmodernism and studio practice. As a result, I analyzed my production in object prints in order to think about a possible unfolding of the print in the expanded field, demonstrating possible relationships between molding, printing and spatiality.